2017
DOI: 10.1177/0098628317727909
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Like a Psychologist Introductory Psychology Writing Assignments

Abstract: Teaching the general psychology course provides instructors with the opportunity to invite students to explore the dynamics of behavior and mental processes through the lens of theory and research. Three innovative writing assignments were developed to teach students to think like a psychologist, operationalized as enhancing critical thinking, applying research concepts, and resisting plagiarism. The assignments were evaluated with two samples of general psychology students. In Sample 1, student reactions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Student regard for the scientific nature of psychology is likewise low and does not improve with progression through the undergraduate career (Holmes & Beins, 2009). At the same time, endorsement of psychological myths is high (Hughes, Lyddy, & Lambe, 2013), and students struggle to think critically (Wentworth & Whitmarsh, 2017).…”
mentioning
confidence: 99%
“…Student regard for the scientific nature of psychology is likewise low and does not improve with progression through the undergraduate career (Holmes & Beins, 2009). At the same time, endorsement of psychological myths is high (Hughes, Lyddy, & Lambe, 2013), and students struggle to think critically (Wentworth & Whitmarsh, 2017).…”
mentioning
confidence: 99%
“…Interventions aimed at supporting student thinking and writing can be found in most disciplines, e.g. psychology (Wentworth et al 2017). Divan et al (2015) found that most international students on a UK master's programme in biology agreed that writing assignments on the course were different from their previous studies.…”
Section: Inclusive Assessment: Practical Implicationsmentioning
confidence: 99%
“…Bartels and Griggs (2019) discuss how recent reexaminations of the Stanford Prison Experiment archives provides opportunities for students to apply scientific inquiry and critical thinking skills to classic studies. Alternatively, as described below, instructors may work backward from summative assessments to build formative assessments that systematically encourage the necessary practice, feedback, and reflection (e.g., Wentworth & Whitmarsh, 2017).…”
Section: Authentic Goal 2 Assessmentsmentioning
confidence: 99%